2018
DOI: 10.3390/su10041057
|View full text |Cite
|
Sign up to set email alerts
|

A 10-Year Statistical Analysis of Heavy Metals in River and Sediment in Hengyang Segment, Xiangjiang River Basin, China

Abstract: Heavy metal elements in water and surface sediments were characterized in Hengyang river segment in Xiangjiang River basin, one of China's most important heavy metal control and treatment region. Data of heavy metal monitoring results in water and sediment for 10 years were acquired from an environmental monitoring program in the main channel of the studied area. Descriptive and exploratory statistical procedures were performed to reveal the characteristics of the sample distributions of heavy metal elements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The lower concentration of other heavy metals is probably related to a less amount of discharge. Table 2 also summarizes the concentration of the examined heavy metals in other reaches of the Xiangjiang River and in other rivers in South China [28,36,[40][41][42]. The distribution of heavy metals is clearly different among different reaches of the Xiangjiang River (including Yongzhou, Hengyang, Zhuzhou, and Changsha).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower concentration of other heavy metals is probably related to a less amount of discharge. Table 2 also summarizes the concentration of the examined heavy metals in other reaches of the Xiangjiang River and in other rivers in South China [28,36,[40][41][42]. The distribution of heavy metals is clearly different among different reaches of the Xiangjiang River (including Yongzhou, Hengyang, Zhuzhou, and Changsha).…”
Section: Resultsmentioning
confidence: 99%
“…The Yongzhou Reach is the upstream and has the lowest concentration of heavy metals (except for Cr) in sediment [28]. The Hengyang Reach is located between Yongzhou and Zhuzhou and has the highest concentration of Cu, Zn, As, and Pb in sediment [40]. For the Zhuzhou Reach, the concentration of Co, Ni in the sediment is generally lower, but the concentration of Cd is the highest.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that sediment could act as an indicator for water pollution, the history and intensity of anthropogenic metal pollution, and ecological changes [11]. Thus, the sediments played an important role in controlling the pollution sources [12][13][14]. Therefore, an evaluation of toxic metal pollution in river sediment is of great value for a study of river ecological environments, as well as prevention and control of river pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metal pollution has become a worldwide environmental concern because of its latency, toxicity, and contamination within soils over time [1]. Heavy metal pollution is generally considered to result from anthropogenic activities, such as mining, mineral fertilizers, vehicle exhaust, and other industrial activities [2,3]. Industrial activities are regarded as the principal contributor for heavy metal pollution [4].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is the best option to use native plants for phytoremediation, as they grow well in the harsh environment. The main objectives of this study were (1) to assess heavy metal pollution through different methods and (2) to identify potential phytoremediator of Cd, Cr, As, Pb, and Cu for phytoremediation in this region.…”
Section: Introductionmentioning
confidence: 99%